THE EFFECT OF RIFAMPICIN DRUG ON LIVER ENZYMES (ALT AND AST) IN RABBITS - Al-Mehdawi, Ferial; Abdul-Lattif, Rashaa; Ali, Intisar (Iraqi Journal of Science, 2024)
The aim of this study was intend to study the effect of rifampicin drug on the level of liver enzymes in rabbits. Eight rabbits were used in this experiment and they were divided into two groups. The first group (control group) was administrated with 15 mg /ml/day normal saline for 35 days, while the second group (treated group) was administrated with 15 mg/ml/day for 35 days of rifampicin capsule (300 mg/kg). This study examined the influences of rifampicin drug on the concentration of Aspartate aminotransferase (ALT), Alanine aminotransferase (AST), total bilirubine and alkaline phosphates in rabbit sera. The results showed that there were a significant increase (p<0.05) in ALT concentration in rifampicin treated group compared with control group, and there were no significant differences in ALT and total bilirubine but there was a significant increase (p<0.05) in alkaline phosphates concentration. It was concluded that rifampicin produced a liver dysfunction .